Persistent alveolar inflammatory response in critically ill patients with COVID-19 is associated with mortality - de Brabander, Justin; Boers, Leonoor S; Kullberg, Robert F J; Zhang, Shiqi; Nossent, Esther J; Heunks, Leo M A; Vlaar, Alexander P J; Bonta, Peter I; Schultz, Marcus J; van der Poll, Tom; Duitman, JanWillem; Nossent, E J; et al. (Thorax, 2023)
IntroductionPatients with COVID-19-related acute respiratory distress syndrome (ARDS) show limited systemic hyperinflammation, but immunomodulatory treatments are effective. Little is known about the inflammatory response in the lungs and if this could be targeted using high-dose steroids (HDS). We aimed to characterise the alveolar immune response in patients with COVID-19-related ARDS, to determine its association with mortality, and to explore the association between HDS treatment and the alveolar immune response.MethodsIn this observational cohort study, a comprehensive panel of 63 biomarkers was measured in repeated bronchoalveolar lavage (BAL) fluid and plasma samples of patients with COVID-19 ARDS. Differences in alveolar–plasma concentrations were determined to characterise the alveolar inflammatory response. Joint modelling was performed to assess the longitudinal changes in alveolar biomarker concentrations, and the association between changes in alveolar biomarker concentrations and mortality. Changes in alveolar biomarker concentrations were compared between HDS-treated and matched untreated patients.Results284 BAL fluid and paired plasma samples of 154 patients with COVID-19 were analysed. 13 biomarkers indicative of innate immune activation showed alveolar rather than systemic inflammation. A longitudinal increase in the alveolar concentration of several innate immune markers, including CC motif ligand (CCL)20 and CXC motif ligand (CXCL)1, was associated with increased mortality. Treatment with HDS was associated with a subsequent decrease in alveolar CCL20 and CXCL1 levels.ConclusionsPatients with COVID-19-related ARDS showed an alveolar inflammatory state related to the innate host response, which was associated with a higher mortality. HDS treatment was associated with decreasing alveolar concentrations of CCL20 and CXCL1.